SISTEM INFORMASI ABSENSI PEGAWAI PADA SMA NEGERI 15 TANGERANG BERBASIS WEB - Nur Azizah; Muhamad Fitra Syawall; Deddy Chandra Fikriansyah (Universitas Insan Pembangunan Indonesia, 2016)
ABSTRACTIn the era of globalization intensified development as well as the increasingly rigorous competition therefore isneed for critical thought to build the human resources (HR). Tantanganpun is getting so complex. Whileprocessing a system of employee attendance information on SMA NEGERI 3 TANGERANG is still done by(manually), not using a computerized attendance system information in the process data. So the information isobtained takes a long time and the storage is not guaranteed. The error occurred because of frequent or losing adata then it came unwanted losses then the application of the computerized system on the system attendanceclerk at SMA NEGERI 3 TANGERANG needs to be done in order to improve the data in an information systemis primarily a system of absentee employees. With a computerized system that dealt with will be able toguarantee the existence of the statutes, the time to produce the information and can control the mechanismautomatically by applying good control and does not require an extensive data for archiving because most of thedata stored in a computer file. While in (manual) are not effective and efficient. during the research the authorusing several methods including: interviews, observation, and study library, the data obtained were analyzed inthe form of the Unified Modeling Language (UML) using visual paradigm''s software 4.0 and in the creation oftheir website using XAMMP.Keyword: Employee Absences, Unified Modeling Language (UML), visual paradigm 6.4 and XAMMP.